Households’ Preferences for Private Tuition Attributes in Jaffna Municipal Area, Sri Lanka - Vanaiya, S.; Sivashankar, S.; Sooriyakumar, K.; Sarujan, S. (National centre for advanced studies in Humanities and Social sciences, 2024)
In Sri Lanka, there has been growing competition for university admission, and due to this, private tuition plays a vital role in many students' educational journeys. This study investigates households' preferences for private tuition attributes and analyzes the socio-economic and demographic factors that influence private tuition attributes in the Jaffna Municipal Area, Sri Lanka. This study considered attributes such as teachers' performance, teaching materials, exam methods, zoom classes, paper classes, and monthly payments to analyze the households’ preferences. For this study, 300 Households of A/L. students were randomly selected from the Jaffna Municipal Area, and data were collected using a structured questionnaire. A discrete choice experiment was employed, and a random parameter logit model was used to estimate the households' preferences for private tuition attributes. The findings of this study reveal that households are willing to pay more for paper classes (LKR 5397), followed by 75% improvements in teachers' performance (LKR 3894), teaching materials (LKR 2217), weekly exams (LKR 1383), and zoom classes (LKR 665). Also, a 50% improvement in teachers' performance and monthly exams are less preferred. Notably, respondents' education and age significantly influence their choice. The findings of this study would be helpful to policymakers in improving the Sri Lankan education system.
Keywords: Discrete choice experiment; Government school; Private tuition; Random parameter logit model; Willingness to pay